Dinotefuran-induced morphophysiological changes in the ovaries and midgut of semi-engorged females Rhipicephalus sanguineus Latreille, 1806 (Acari: Ixodidae) ticks - de Oliveira, Patrícia Rosa [UNESP]; Remédio, Rafael Neodini [UNESP]; Bechara, Gervásio Henrique [UNESP]; Anholeto, Luis Adriano [UNESP]; Mathias, Maria Izabel Camargo [UNESP] (Springer Nature, 2016)
The present study demonstrated the effects of dinotefuran (active compound of the Protetor Pet® acaricide) in germ cells and the digestive processes of semi-engorged females of R. sanguineus exposed to different concentrations of the chemical. For this purpose, 120 semi-engorged females were divided into four treatment groups with 30 individuals each: group I or control (distilled water), group II (5000 ppm), group III (6250 ppm), and group IV (8334 ppm of dinotefuran). All ticks were immersed in different concentrations of dinotefuran or in distilled water for 5 min and then were dried and stored in biological oxygen demand (BOD) incubator for 7 days. The results show the action of this compound, exhibiting morphohistologic and histochemical changes in the oocytes and the midgut cells of individuals of different groups, which were compared with those of group I (control). The alterations occurred mainly in relation to the size of the germ cells and yolk granules; presence, quantity, size, and location of vacuoles found in the cytoplasm of these germ cells; the damage occurred in the generative cells of the midgut; the size of the digestive cells; the quantity of blood elements captured, accumulated digestive wastes and digestive vacuoles found in the cytoplasm of the digestive cells of the midgut, as well as the amount and distribution of proteins, polysaccharides, lipids of all cells in both organs. So, it has demonstrated the effectiveness of dinotefuran in the reduction of fertility and digestive processes of semi-engorged females of R. sanguineus, data that points the possibility of employing this chemical to control these ectoparasites.
Keywords: Acaricide; Dinotefuran; Neonicotinoids; Rhipicephalus sanguineus; Tick